Analisis Kesesuaian Pemanfaatan Ruang di Kecamatan Cianjur - Titan Kesuma Endasmoro; Lely Syiddatul Akliyah (Jurnal Riset Perencanaan Wilayah dan Kota, 2023)
Abstract. The increase in population from year to year is increasingly irregular so that the need for land for residential areas also increases. As a result, the people of Cianjur District built a residential area on a spatial pattern plan that was not intended for it. Another factor of the discrepancy in the use of the space is the ignorance of the community about the spatial plan. The government of Cianjur Regency has yet to socialize the spatial plan down to the village or kelurahan level. The purpose of this study is to analyze the suitability of space utilization. This research uses quantitative methods. The method used for this research is the method of map overlay and observation of satellite imagery. The results of the overlay with the RTRW spatial pattern plan show that the number of unsuitable polygons for spatial use is 36 polygons with a total area of 3.92 Ha. Based on the results of the analysis, so that the Cianjur Regency government can immediately follow up on space utilization that is not in accordance with the pattern plan, besides that the government must carry out socialization regarding the spatial plan, as well as evaluate the Cianjur Regency Spatial Plan for 2011-2031 and the Urban Area RDTR Draft Cianjur. Abstrak. Peningkatan jumlah penduduk dari tahun ke tahun semakin tidak teratur sehingga kebutuhan akan lahan untuk kawasan permukiman pun ikut meningkat. Akibatnya masyarakat Kecamatan Cianjur membangun suatu kawasan permukiman pada rencana pola ruang yang bukan peruntukkannya. Faktor lainnya dari ketidaksesuaian pemanfaatan ruang tersebut adalah ketidaktahuan masyarakat mengenai rencana tata ruang. Pemerintah Kabupaten Cianjur pun belum melakukan sosialisasi mengenai rencana tata ruang hingga ke level desa atau kelurahan. Tujuan dalam penelitian ini adalah menganalisis kesesuaian pemanfaatan ruang. Penelitian ini menggunakan metode kuantitatif. Metode yang digunakan untuk penelitian ini adalah metode pertampalan peta dan pengamatan citra satelit. Hasil overlay dengan rencana pola ruang RTRW menunjukkan bahwa jumlah poligon ketidaksesuaian pemanfaatan ruang berjumlah sebanyak 36 poligon dengan total luasan 3,92 Ha. Berdasarkan hasil analisis, agar pemerintah Kabupaten Cianjur dapat segera menindaklanjuti pemanfaatan ruang yang tidak sesuai dengan rencana pola, selain itu pemerintah harus melakukan sosialisasi terkait rencana tata ruang, serta melakukan evaluasi terhadap Rencana Tata Ruang Wilayah Kabupaten Cianjur Tahun 2011-2031 dan Draft RDTR Kawasan Perkotaan Cianjur.